Sympathetic Nervous System Activity in Preschoolers Who Stutter - Walsh, Bridget; Smith, Anne; Christ, Sharon L.; Weber, Christine (Frontiers in Human Neuroscience, 2019)
Background In our Dynamic Pathways, account, we hypothesized that childhood stuttering reflects an impairment in speech sensorimotor control that is conditioned by cognitive, linguistic, and emotional factors. The purpose of this study was to investigate potential differences in levels of sympathetic arousal during performance of speech and non-speech tasks between children who do and do not stutter. Methods Seventy-two preschool-aged children participated in the study, 47 children who stutter (CWS; 38 boys) and 25 children who do not stutter (CWNS; 18 boys). We recorded skin conductance and blood pulse volume (BPV) signals, indices of sympathetic arousal, during higher/lower load speech tasks (structured sentence production and picture description) and non-speech tasks (jaw wagging and forceful blowing). We included a measure that reflects children’s attitudes about their communication skills and a parent-report assessment of temperament. Results We found no significant differences between preschool CWS and CWNS in phasic skin conductance response amplitude or frequency, BPV, and pulse rate for any of the experimental tasks. However, compared to CWNS, CWS had, on average, significantly higher skin conductance levels (SCL), indexing slowly changing tonic sympathetic activity, across both speech and non-speech experimental conditions. We found distinctive task-related profiles of sympathetic arousal in both groups of preschool children. Most children produced the highest levels of sympathetic arousal in the physically demanding blowing task rather than in speech, as seen in previous studies of adults. We did not find differences in temperament between the two groups of preschool children nor a relationship among behavioral indices of temperament and communication attitude and physiological measures of sympathetic arousal. Conclusion We did not find that atypically high, speech-related sympathetic arousal is a significant factor in early childhood stuttering. Rather, CWS had higher, on average, task-related tonic SCLs across speech and non-speech tasks. A relationship among behavioral measures of temperament and physiological measures of sympathetic arousal was not confirmed. Key questions for future experiments are how the typical coupling of sympathetic and speech sensorimotor systems develops over childhood and adolescence and whether task related developmental profiles follow a different course in children who continue to stutter.